The resistance status of Anopheles gambiae s.l. in Chikwawa district, Southern Malawi - Miss Shupikai Kambiring'oma; Miss Judith Banda; Dr Elizabeth Bandason; Dr Themba Mzilahowa; Mr Owen Ndalama (International Journal of Infectious Diseases)
Introduction: Chikwawa district is an area of high malaria transmission as it harbors three abundant anopheline species namely: An. gambiae s.s, An. funestus s.s and An. arabiensis. Despite the adoption of malaria control interventions which includes indoor residual spraying (IRS), insecticide-treated bed nets (ITN) and intermittent preventative therapy for pregnant women (iPTp), the district still has high cases of malaria. Moreover, Chikwawa has registered multiple insecticide resistance cases which is of huge threat to the malaria control interventions in Malawi. This study determined the resistance status of An. gambiae s.l to pyrethroids in Chikwawa district. Methods: Mosquito larvae from Lisuli and Nchalo sites in Chikwawa district were sampled and reared to adults in the insectary. The WHO tube assay was conducted using permethrin (0.75%), deltamethrin (0.05) and alpha-cypermethrin (0.05%). 3-5 days old Anopheles gambiae s.l. were exposed to the insecticides for 1 hour. Knockdown was recorded every 10 minutes for 1 hour and mortality was recorded at 24 hours’ post-exposure. Results: Anopheles gambiae s.l was resistant to alpha-cypermethrin (18%) followed by permethrin (12%) and lower to deltamethrin (2%) in Nchalo site. However, mosquitoes were susceptible to alpha-cypermethrin (97%), deltamethrin (99%) and permethrin (98%) in Lisuli site. Discussion: The observed resistance confirms resistance of An.gambiae species to pyrethroids with moderate intensities in Lisuli and high resistance intensities in Nchalo. The observed alphacypermethrin resistance could be due to pre-exposure to the chemical, cross resistance or kdr mechanisms in An.gambiae as observed in similar studies. Permethrin resistance could be attributed to the presence of detoxifying enzyme in the An.gambiae population used in the study. Conclusion: Strategies to manage insecticide resistance particularly against pyrethroids must be scaled up. These include the continued distribution of PBO nets on a wide scale to reach most parts of Chikwawa district and Malawi as a whole. Use of duo nets such as Interceptor G2 and Royal guard nets is also encouraged to manage the growing Insecticide resistance. This will help deter malaria control challenges and overall improve progress towards malaria elimination.